The influence of intermittent fasting on the circadian pattern of melatonin while controlling for caloric intake, energy expenditure, light exposure, and sleep schedules : a preliminary report - Almeneessier, Aljohara S. (2017)
Fil: Almeneessier, Aljohara S. King Saud University. College of Medicine. Department of Family and Community Medicine; Arabia Saudita